Exploring Gender Differences in Self‐Regulation: Interactive Effects of Mood and Self‐regulatory Focus - Sharma, Piyush (2019)
In this research, the author explores a wide range of risky behaviors among college students and highlights some important gender differences in the complex socio-psychological processes underlying these behaviors. First, based on prior research it is suggested that men are more likely than women to indulge in risky behaviors in general however there are significant differences between the men and women in the influence of mood on their risky behaviors. Positive mood is shown to affect both the genders in a similar manner whereas under negative mood men are more likely to indulge in risky behaviors compared to women. Next, it is argued that the influence of promotion focus is stronger on men compared to the women whereas women are more likely to be influenced by prevention focus compared to men. This is because most women are brought up on the notion that it is not socially acceptable for girls to indulge in "manly" activities whereas boys are specifically motivated to participate in adventure-seeking, physical activities. Finally, it is suggested that even a highly promotion-focused female would be less inclined to indulge in risky behaviors compared to a moderately promotion-focused male and vice versa. Results from an empirical study are reported and some directions for future research are suggested.